The Influence of Different Curcuma zanthorrhiza Dosage To The Growth and Survival Rate Of Nile Tilapia (Oreochromis niloticus) - Linayati Linayati; Muhammad Bahrus Syakirin; Hayati Soeprapto (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2021)
The research was held in 14th July  – 20th August 2018. Located in Brackish water Laboratory, Fisheries Faculty of Pekalongan University. The aim of this research is to find out the impact of curcuma to increase the growth and survival rate of Nile Tilapia. The treatment that be implemented was extending dosage of curcuma flour (gram)  in 1 kg of artificial  fish feed, such as followed : treatment A 0 ml ( control), B  9 g  of curcuma, C 12 g  curcuma and D 15 g curcuma. The method used was the Completely Randomized Design Method consisting of 4 treatments and 3 replications. The result which had given from the research was treatment D showed the highest growth.  The average of weight of fish which can be reached by every treatment A, B, C, D as described 3,31 g, 4,77 g, 6,8 g, and 8.04 g, The analysis of result showed that all treatments have different effects for growth of fish. The water quality during the research such as temperature between 27-290 C, pH revolve 7,1-7,3 and the salinity was 16-17 ppt which mean all parameters was supported to fish growth.